Electrochemical heteroarylation and amidation of alkanes using activated glassy carbon electrodes without mediators - Loris Laze; Jose C. Gonzalez-Gomez; Irene Bosque (Communications Chemistry)
Abstract The functionalization of challenging unactivated C(sp 3)–H bonds was achieved electrocatalytically via hydrogen atom transfer and without mediators. This was possible through the sole activation of the surface of the Glassy Carbon Electrode (GCE) in an electrochemical fashion using a phosphate buffer. This activation produced oxygenated functional groups on the surface, capable of abstracting these hydrogen atoms from C(sp 3)–H of alkanes. Minisci and Ritter-type reactions were achieved using this procedure. Extensive characterization of the activated GCE (AGCE) and preliminary mechanistic studies allow us to propose plausible reaction mechanisms. Furthermore, a regular battery can be used within this protocol to achieve the desired substituted alkanes under inexpensive and user-friendly conditions.